Muscle echo intensity: reliability and conditioning factors - Caresio, Cristina; Molinari, Filippo; Emanuel, Giorgio; Minetto, Marco Alessandro (Clinical physiology and functional imaging, 2015)
Summary Objective To assess the issue of muscle echo intensity reliability and to investigate the relationship between muscle echo intensity and size, shape and location of the region of interest (ROI) used for echo intensity quantification. Methods Ultrasonographic scans of the following five muscles were acquired in twenty healthy subjects: biceps brachii, rectus femoris, vastus lateralis, tibialis anterior and medial gastrocnemius. Muscle echo intensity was quantified in each scan. Results We found that the agreement between the different sized ROIs considered in each scan ranged from moderate (ICC: 0·54) to high (ICC: 0·86) and that the echo intensity consistency between equal sized ROIs of the three scans ranged from low (ICC: 0·42) to very high (0·91). The echo intensity of tibialis anterior and rectus femoris was different between different sized, shaped and located ROIs. The echo intensity of biceps brachii and tibialis anterior was higher than that of all other muscles, and females had higher echo intensity than males. Moreover, the muscle echo intensity was positively correlated with the subcutaneous layer thickness in three of five muscles. Conclusion The echo intensity reliability was function of the ROI size. Muscle and gender variability in echo intensity was likely due to differences in fibrous and adipose tissue content and distribution. Possible explanations for the observed correlations between muscle echo intensity and subcutaneous layer thickness include the dependence of both variables on total body adiposity or the direct dependence of the extent of intramuscular fat on the amount of subcutaneous fat.